Sensory Characteristics of Wet Noodles Substituted with Yam Flour (Dioscorea alata) as an Alternative Functional Food for Diabetic Patients - Tysa Runingsari; Nikita Welandha Prasiwi; Hilmia Salma Putri (Media Gizi Kesmas, 2026)
Background: Diabetes mellitus is on the rise in Indonesia largely due to dietary habits characterized by a high intake of refined carbohydrates and a low intake of dietary fibre. This situation underscores the need for alternative food products that are not only beneficial in terms of their nutritional content but also acceptable to consumers. Yam (Dioscorea alata) is a locally grown food known to be rich in fibre and has a low glycemic index, making it suitable for development as a functional food ingredient. Wet noodles can be prepared using yams to partially replace wheat flour through the incorporation of yam flour, the sensory properties of which require evaluation. Objectives: This paper sought to test the sensory or organoleptic properties of wet noodles substituted with yam flour as a functional food alternative for patients with diabetes mellitus. Methods: The approach was a true experimental designed with Completely Randomized Design (CRD) with four ratios of wheat flour and yam flour: P0 (100:0), P1 (70:30), P2 (50:50), and P3 (30:70), each with six repetitions. Organoleptic evaluation was conducted using hedonic and ranking tests that evaluated colour, aroma, taste, and texture involving semi-trained panelists. The Kruskal Wallis test was used to analyse the data. Results: Substitution with yam flour resulted in a significant difference in colour and texture parameters (p<0,05), but no significant difference was found in aroma and taste among formulations. Increasing levels of substitution resulted in gave a darker colour and less elasticity. Nutritional analysis showed that P3 (70% yam flour substitution) exhibited the highest functional value, with the highest fibre content (7.06 g/100 g) and the lowest carbohydrate content (51.26 g/100 g). However, based on the effectiveness index formulation P1 (70% wheat flour:30% yam flour) was found to be the most acceptable based on the ranking test. Conclusion: In wet noodle formulations, substitution of up to 30% yam flour did not negatively affect sensory characteristics and demonstrates the potential to be developed as a functional food alternative for patients with diabetes mellitus.